The Possibility of Coherentism and the Stringency of Ceteris Paribus Conditions - Schupbach, Jonah N. (THEORIA. An International Journal for Theory, History and Foundations of Science, 2015)
Schupbach (2008) puts forward a "possibility result" for Bayesian Coherentism, showing that there exist plausible sets of ceteris paribus conditions that imply that coherence is truth-conducive. Against this result, Schubert (2012) has argued that Schupbach’s considered ceteris paribus conditions are "jointly inconsistent". In this article, I first show that Schubert’s attempted proof of this claim is fallacious, and hence that the possibility result still stands. Next, I consider a related criticism of Schupbach’s result, inspired by Olsson’s (2005) constraints on ceteris paribus conditions. This leads to a general discussion of the principle(s) that should guide one in choosing such conditions.